Free-space optical mode division multiplexing for switching between millimeter-wave picocells - Amphawan, Angela; Chaudhary, Sushank (2015)
For connectivity between millimeter-wave radio femtocells or picocells, a free-space optical link may be used in a ubiquitous radio-over-free-space-optics (Ro-FSO) platform.This work introduces a new optical Hermite-Gaussian mode division multiplexing scheme for multiplexing radio signals between different picocells in a Ro-FSO network using a spatial correlator.Distinct 2.5GHz 10GHz radio-modulated subcarrier data streams from two picocells over two 850nm optical Hermite-Gaussian mode carriers were successfully multiplexed to two picocells separated by 500 meters. At the receiver, the signals were retrieved on the two modes using nonintermetric decomposition and spatial correlation optical Hermite-Gaussian modes into linearly polarized modes.Optical signal-to-noise ratios, bit-error-rates and modal decomposition results demonstrate effective data transmission between the picocells.